Mycoplasmosis in poultry: update on diagnosis and preventive measures. Issue 1 (1st March 2017) - Umar, S.; Munir, M.T.; Ur-Rehman, Z.; Subhan, S.; Azam, T.; Shah, M.A.A.
Abstract : Avian mycoplasmas occur in a wide variety of birds including commercial poultry. The most important mycoplasmas in chickens and turkeys are Mycoplasma gallisepticum (MG), M. synoviae (MS), and M. meleagridis . Additionally, M. iowe (MI) is an emerging pathogen in turkeys, but appears to pose little issues for chickens. Pathogenic mechanisms include adherence to host target cells, release of toxins, mediation of apoptosis and immune evasion leading to obstruction of the tracheal lumen, exfoliation of epithelial cells as well as ciliostasis. In addition, mycoplasma by-products, such as hydrogen peroxide and superoxide radicals, along with inflammatory cytokines can exacerbate the disease conditions. Mycoplasmas are transmitted horizontally, from bird to bird, and vertically, from dam to offspring through the egg. The disease is diagnosed by serologic tests, cultures and PCR and is sensitive to antimicrobials whose activity is other than disrupting the bacterial cell wall. Control of pathogenic avian mycoplasmas can consist of one of three general approaches; maintaining flocks free of infection, medication, or vaccination, which are covered in this review.